Faktor-Faktor yang Mempengaruhi PUS Memilih KB Alamiah di Desa Binturu, Kecamatan Larompong - Hadija Hadija; Jumriana Ibriani; Astuti Suardi; Ulvy Pratiwy D; Devianti Tandiallo (JIK-JURNAL ILMU KESEHATAN, 2022)
Natural Contraception (KBA) is to regulate the distance of birth of children, regulate inspiration by not using tools, chemicals or drugs. The percentage of kb participants in Indonesia in 2016 was 33.72%, this figure is lower than the achievement in 2015 of 38.75%. In 2016 in South Sulawesi with a proportion of 71.71% were Couples of Childbearing Age who participated in birth control. Based on the participants of birth control the contraceptives used were Injectable (47.39%), Pills (22.90%) Implant (8.84%), MOW (1.04%), IUD ( 3.21%) Condoms (13.45%) and simple methods (0.28%). This study is to find out what factors affect PUS choosing natural birth control in Binturu Village, Larompong District in 2021.This study uses a quantitative approach with an observational type of research, with a sample of 35 people (Total Sampling)., analysis of univariate and bivariate data using the Chi-Square Test. The results showed that the factors related to the selection of contraceptive methods were Education ρ = 0.292 (ρ>0.05), Knowledge ρ = 0.075 (ρ>0.05), and husband support ρ = 0.267 (ρ<0.05). The results of this study education and knowledge have no relationship with the selection of natural birth control contraceptive methods, and husband support has no relationship with the selection of natural birth control contraceptive methods, it is expected for couples of childbearing age Need increased knowledge about the types of contraceptives, benefits of contraception, side effects of using contraceptives and the consequences of not using contraceptives